Teachers’ Written Corrective Feedback Strategies Through the Lens of the Students - Christian Jay O. Syting; John Rick Malisobo; Marivic Salce; Michael Roasol (CV. Tripe Konsultan, 2023)
This descriptive-qualitative study was conducted to venture the written corrective feedback strategies employed by the College of Teacher Education teachers in a private university in Davao City, Philippines. The study utilized thematic analysis to analyze the data gathered from the in-depth interviews of eight selected participants through a purposive sampling technique. The data revealed teachers' seven written corrective feedback strategies: lexical written feedback, grammatical written feedback, organization in writing, motivating written feedback, metalinguistic feedback, and verification feedback. Additionally, this study uncovered the impact of written corrective feedback strategies, namely improvement of lexical skills, improvement of sentence structure, improvement of grammatical skills, development of the organization in writing, enhancement of self-regulation, a decrease of the affective filter, and improvement of learning productivity. The results of this study presented various written corrective feedback strategies for the teachers. It also unveiled the implications of the strategies employed. Hence, it is gainful for the administrators and teachers because they will be encouraged to use the strategies found in the study and practice them in the academe. It will also contribute to the students in a way that they will value the feedback.